Electrochemical and adsorption properties of novel phthalocyanines with four 16-membered diazadithia macrocycles - (:unkn) unknown (JOHN WILEY & SONS LTD, 1998)
Cyclic voltammetric measurements of Cu(II) and Ni(II) phthalocyanines with four 16-membered diazadithia macrocycles (1 and 2) and pentanuclear Ni(II) phthalocyanine bearing four Cu(II) ions in diazadithia macrocycles at the peripheral positions (3) have been carried out on platinum in DMSO and in aqueous medium 3 showed strong adsorption properties in DMSO and especially in aqueous medium, possibly as a result of the interaction between the copper ions in the four macrocycles and the platinum working electrode. Interestingly, the oxidation peak of 3 was split into two waves in aqueous medium. This behaviour is discussed in terms of disaggregation of the mixed valence species produced by the oxidation of aggregated species. A mechanism for both the oxidation of the complex and the splitting of the oxidation peak into two waves is suggested. (C) 1998 John Wiley & Sons, Ltd.
Keywords: phthalocyanines; diazadithia macrocycles; cyclic voltammetry; adsorption properties; redox potentials; GRAPHITE-ELECTRODES; O-2 REDUCTION; DERIVATIVES; OXYGEN; FILMS